Bone drugs in pediatrics : efficacy and challenges - Klein, Gordon L. (Springer US, 2014)
Bone Drugs in Pediatrics brings together in one place the evidence for the use of certain drugs in the treatment and prevention of bone loss in children, as well as the reservations still present in the pediatric community regarding their use. Beginning with a discussion of developmental pharmacokinetics and drug development for pediatric diseases where bone loss occurs, such as osteogenesis imperfecta, the physiology of pediatric bone and how best to monitor the safety and efficacy of these drugs is presented. The pros and cons of utilizing the drugs themselves - such as bisphosphonates, anti-resorptives and anabolic agents - within the pediatric population are carefully considered, with an eye toward safe and effective integration. The potential use of drugs in future treatment is also highlighted. On the whole, Bone Drugs in Pediatrics is a cogent presentation of the ongoing debate surrounding the potential for pharmacological interventions in pediatric bone loss.